Práticas pedagógicas em educação ambiental mediadas por tecnologias digitais: uma experiência de formação compartilhada explorando/construindo o material educonexão - Carmo, Amanda Amália Araújo do (2019)
The general objective of this qualitative research was to investigate how a group of teachers builds or appropriates the teaching knowledge put into motion in shared training practices that deal with local socio-environmental issues mediated by Digital Technologies. In view of the above, this work was guided by the following research question: What relationships do teachers establish with the knowledge mobilized and / or built in a process of shared formation when developing pedagogical practices in Environmental Education (EA) under the mediation of Digital Technologies? For this, we developed meetings of shared formation in a school with 12 teachers of elementary education II, divided in two stages: stage I construction of the website Educonexão by the author of the research to divulge the material produced in the meetings and stage II consisted in the planning phase and discussions of the activities with the theme of the local Environmental Education mediated by the Digital Technologies. The instruments of data production were: audio recording, field diary and the activities produced. During the treatment of the data we seek: (I) to analyze the set of pedagogical practices developed and (II) to identify the relationship that teachers establish with the knowledge mobilized in the construction of activities. After the data were transcribed, they were printed in the form of tables and we performed a systematic reading in order to analyze the recurrences in the teachers' speeches, in initial, general and finally categories of analysis. The analysis of the content allowed delimiting, two categories of analyzes "The education of the education by the shared formation: the voice of the professors" and "The mediation of the digital technologies in the teaching: possibilities of ‗Educonexão‘". As a result of the research we have the construction of the website ―Educonexão‖, which gathers information about the remnants of the natural heritage of Divinópolis MG, discussions. Notes on how to make Critical Environmental Education teaching in the school context through the vision of a group of teachers with many years of experience and, finally, the construction of the topic "suggestion of activities" in "Educonexão", to disseminate pedagogical practices developed in order to assist other teachers in the preparation of their classes with the theme of local Environmental Education.